A Solitary Rectal Retention Polyp in an Adult Patient with Ulcerative Colitis: A Case Report - Abbas Ahmadifar; Hoda Imani (Case Reports in Clinical Practice, 2026)
Retention polyps, also known as juvenile polyps, are non-neoplastic hamartomatous lesions. Their occurrence in adults is rare, and finding a solitary retention polyp in a patient with underlying inflammatory bowel disease (IBD) is exceptionally uncommon. We report the case of a 42-year-old male with a 9-year history of ulcerative colitis, currently in clinical and endoscopic remission (Mayo Endoscopic Score 1) on mesalamine therapy. During a routine surveillance colonoscopy, a solitary, asymptomatic, 15 mm sessile polyp with a smooth, cystic appearance was discovered in the rectum. The lesion was removed via endoscopic mucosal resection (EMR). Histopathological evaluation revealed no evidence of dysplasia or malignancy, confirming the diagnosis of a retention polyp. Although rare, retention polyps should be considered in the differential diagnosis of solitary polyps in adult patients with UC. Complete endoscopic resection and precise histopathological examination are essential to rule out dysplasia and guide appropriate management.